Can Generic Science Skills be Improved through Physics Learning Media with PjBL Model? (A Review) - Aris Doyan; Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti (Jurnal Penelitian Pendidikan IPA, 2025)
Project-Based Learning (PjBL) physics learning media has emerged as an effective strategy for improving students' generic science skills. This research aims to identify and analyze research trends of improving generic science skills through physics learning media with PjBL model. This research method is descriptive and analytical. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on improving generic science skills through physics learning media with PjBL model that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. Research trend with an increase in the number of publications from 2015 to 2018. However, in 2019 and 2022 the research trend on the generic science ability in learning has decreased from the previous year and the research trend increase again in 2023. There are many documents in the form of articles, proceedings, book chapters and edited books that discuss research improving generic science skills physics learning media with PjBL model. Key words that are often used in research of generic science are critical thinking, e module, science learning, PBL, etc.